Sistem Perubahan Struktur Silabel dan Netralisasi Vokal dalam Bahasa Sasak Dialek Bayan (System Of Syllable Structure Change And Vocal Neutralization In Sasak Dialect Of Bayan Language) - Arifiani, Evi (Balai Bahasa Jawa Tengah, 2019)
The purpose of this study was to find out the various phonological processes in the affixation process in the formation of verbs in the Bayan dialect Sasak language. The method of data analysis with the Agih method and equivalent. Agih method with the technique of sorting out elements directly. The researcher sorted out the affixes forming verbs and Bayan dialect of Sasak verbs. Then, the researcher used the matching method with the direct element sorting technique whose elemental breaker was in the form of an articular phonetic fragment. After that, the researcher describes the phonological processes that occur according to their type with Schane's generative phonological theory (1992). The result of this study shows that the influence of sound around the environment can make the other sounds appear that have the closest characteristics. This led to the phonological process in the form of changes in the structure of the syllable and vocal neutrality. First, In the verb word morphophonemic process with the affixation of the prefix /b?-/ indicating the phonological process in the form of changes in the syllable structure in the form of consonant sound insertion [r], and [l]. Second, In the verb word morphophonemic process with affixation / -a? / showing the phonological process in the form of a change in syllable structure in the form of semi vowel sound insertion [w], and [y]. Third, A case of neutralization occurs when the sound [?] is pronounced to sound [a], if the sound [?] at the end position meets the vowel [a]. The distinguishing or distinctive feature that is neutralized is the characteristic [+ tense] of the sound [?] to [-tense] or [+ lax]. [-Tense] or [+ lax] are the effects of vowels [a].Keywords: verbs, Bayan dialect Sasak language, changes in silabel structure of sound, and sound neutralization